Pengaruh penerapan komunikasi perubahan perilaku dengan model komunikasi antar pribadi pada masyarakat sasaran dalam pelaksanaan gizi spesifik terhadap pencegahan stunting - Hafrina, Hafrina; Maulida, Maulida (Poltekkes Kemenkes Kupang, 2023)
Background: Nutrition problems are still a major concern in Indonesia and have a serious impact on the quality of human resources (HR). This research aims to determine the effect of implementing behavior change communication using the interpersonal communication model. The research design used was Quasy Experiment. The population was 48 people. The sampling technique was total sampling. There is an influence of implementing behavior change communication using an interpersonal communication model in the target community in implementing specific nutrition on stunting prevention (P < 0.05).